A duke in time - MacGregor, Janna (St. Martin's Paperbacks, 2021)
After her husband Meri's death, businesswoman Katherine Vareck discovers that he married two other women and develops a friendship with these women while developing strong feelings for Meri's brother, the Duke of Ranford.